Real‐Time Data and Predictive Analytics: Where Does IR Fit?. Issue 185 (2nd February 2021) - Larkan‐Skinner, Kara; Shedd, Jessica M.
Abstract: As institutions seek to shift into more advanced analytics and data‐based decision‐support, many institutional research offices face the challenge of meeting the office's current demands while taking on more intricate and specialized work to support decision‐making. Given the great need organizations have for information that supports real‐time strategic decision‐making, institutions must advance beyond traditional static data reporting offices to modern offices with regular predictive analytics use. The authors believe that institutional research offices should actively engage in contemporary analytical approaches and provide leadership in this area. The following chapter focuses on (a) why higher education should embrace analytics, (b) discusses areas where analytical advancements have occurred, (c) discusses areas where analytical growth is lacking, and (d) provides guidance on addressing cultural changes concerning institutional data use, policies, and practices.